(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes and discusses issues related to the political, social and cultural situation of Movarounnahr during the reign of the Temurides, the contribution of prominent representatives of the dynasty to the development of the social and cultural life of society, the process of the emergence and formation of the Temurid Renaissance, and in it the place of scientists and literature of Movarounnahr.